Differential Mitochondrial Adaptation of the Slow and Fast Skeletal Muscles by Endurance Running Exercise in Streptozotocin-Induced Diabetic Mice - Takemura, A; Matsunaga, Y; Shinya, T; Matta, H (Physiological research, 2024)
The skeletal muscle is the main organ responsible for insulin action, and glucose disposal and metabolism. Endurance and/or resistance training raises the number of mitochondria in diabetic muscles. The details of these adaptations, including mitochondrial adaptations of the slow and fast muscles in diabetes, are unclear. This study aimed to determine whether exercise training in streptozotocin (STZ)-induced mice leads to differential adaptations in the slow and fast muscles, and improving glucose clearance. Eight-week-old mice were randomly distributed into normal control (CON), diabetes (DM), and diabetes and exercise (DM+Ex) groups. In the DM and DM+Ex groups, mice received a freshly prepared STZ (100 mg/kg) intraperitoneal injection on two consecutive days. Two weeks after the injection, the mice in the groups ran on a treadmill for 60 min at 20 m/min for a week and subsequently at 25 m/min for 5 weeks (5 days/week). The analyses indicated that running training at low speed (25 m/min) enhanced mitochondrial enzyme activity and expression of lactate and glucose transporters in the plantaris (low-oxidative) muscle that improved whole-body glucose metabolism in STZ-induced diabetic mice. There were no differences in glucose transporter expression levels in the soleus (high-oxidative) muscle. The endurance running exercise at 20-25 m/min was sufficient to induce mitochondrial adaptation in the low-oxidative muscles, but not in the high-oxidative muscles, of diabetic mice. In conclusion, the present study indicated that running training at 25 m/min improved glucose metabolism by increasing the mitochondrial enzyme activity and glucose transporter 4 and monocarboxylate transporter 4 protein contents in the low-oxidative muscles in STZ-induced diabetic mice.
Keywords: fyzická vytrvalost; Male; Physical Conditioning, Animal; svalová vlákna typu II; experimentální diabetes mellitus; streptozocin; Adaptation, Physiological; krevní glukóza; kondiční příprava zvířat; Mitochondria, Muscle; Muscle, Skeletal; mužské pohlaví; Muscle Fibers, Slow-Twitch; fyziologická adaptace; Streptozocin; svalové mitochondrie; kosterní svaly; běh; Animals; Physical Endurance; zvířata; myši; Muscle Fibers, Fast-Twitch; Running; Diabetes Mellitus, Experimental; svalová vlákna typu I; Mice; Blood Glucose